Strategi dan Analisis PT indofood dalam Menghadapi Persaingan Industri - Abdurrahman Abdurrahman; Dwi Nur Zahara; Aryo Seno Khusnul R; Titi Salma; Naerul Edwin Kiky Aprianto (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
In the era of globalization, companies are increasingly competitive and are required to have a good business strategy so that companies can remain competitive and develop. Innovation and improving product quality are needed by companies in the face of increasingly fierce competition. Strategy is an important thing in a business. To achieve its goals or objectives effectively and efficiently, the company must be able to deal with any problems or obstacles that arise. The focus of this research refers to PT Indofood Sukses Makmur Tbk. The purpose of this study is to discuss the strategy and analysis of PT Indofood in facing industry competition. The research method used is descriptive qualitative to analyze the competitive strategy used by PT Indofood. Data collection using literature review related to this research. The results of the discussion show that PT Indofood implements various strategies, such as product diversification, increasing operational efficiency, and market expansion through international market penetration. The main finding of this study is the success of PT Indofood in utilizing its competitive advantage to compete in the global market.